Acquired partial lower urinary tract obstruction caused by intravesical ureterocele in an adult dog. (24th February 2022) - Uva, A.; Gernone, F.; Cavalera, M. A.; D'Ippolito, P.; Ricciardi, M.; Carelli, G.; Zatelli, A.
Abstract : Ureterocele is an uncommon condition in dogs characterised by a cystic dilation of the submucosal portion of the distal ureter. A 4‐year‐old intact male Siberian husky with a 4‐month previous diagnosis of ureterocele was presented for pollakiuria. Abdominal ultrasound showed increased dimensions of the ureterocele, and a retrograde positive contrast urethrocystography detected a filling defect of the bladder neck lumen. The position of ureterocele was considered responsible for the partial urinary obstruction. This hypothesis is supported by the resolution of pollakiuria after surgical ureterocele resection. Based on a literature search, this is the first case of an intravesical ureterocele causing partial urinary obstruction in dogs. Ureterocele should be considered as a differential diagnosis in patients with pollakiuria.